Using real interpolation method for adaptive identification of nonlinear inverted pendulum system - Phu Tran Tin; Tran Hoang Quang Minh; Tran Thanh Trang; Nguyen Quang Dung (Institute of Advanced Engineering and Science, 2019)
In this paper, we investigate the inverted pendulum system by using real interpolation method (RIM) algorithm. In the first stage, the mathematical model of the inverted pendulum system and the RIM algorithm are presented. After that, the identification of the inverted pendulum system by using the RIM algorithm is proposed. Finally, the comparison of the linear analytical model, RIM model, and nonlinear model is carried out. From the results, it is found that the inverted pendulum system by using RIM algorithm has simplicity, low computer source requirement, high accuracy and adaptiveness in the advantages.